Organized crime groups: A systematic review of individual‐level risk factors related to recruitment. Issue 1 (11th February 2022) - Calderoni, Francesco; Comunale, Tommaso; Campedelli, Gian Maria; Marchesi, Martina; Manzi, Deborah; Frualdo, Niccolò
Abstract: Background: Studies from multiple contexts conceptualize organized crime as comprising different types of criminal organizations and activities. Notwithstanding growing scientific interest and increasing number of policies aiming at preventing and punishing organized crime, little is known about the specific processes that lead to recruitment into organized crime. Objectives: This systematic review aimed at (1) summarizing the empirical evidence from quantitative, mixed methods, and qualitative studies on the individual‐level risk factors associated with the recruitment into organized crime, (2) assessing the relative strength of the risk factors from quantitative studies across different factor categories and subcategories and types of organized crime. Methods: We searched published and unpublished literature across 12 databases with no constraints as to date or geographic scope. The last search was conducted between September and October 2019. Eligible studies had to be written in English, Spanish, Italian, French, and German. Selection Criteria: Studies were eligible for the review if they: Reported on organized criminal groups as defined in this review. Investigated recruitment into organized crime as one of its main objectives. Provided quantitative, qualitative, or mixed methods empirical analyses. Discussed sufficiently well‐defined factors leading to recruitment into organized crime. Addressed factors at individual level. For quantitative or mixed‐method studies, the study design allowed to capture variability between organized crime members and non‐members. Data Collection and Analysis: From 51, 564 initial records, 86 documents were retained. Reference searches and experts' contributions added 116 additional documents, totaling 202 studies submitted to full‐text screening. Fifty‐two quantitative, qualitative, or mixed methods studies met all eligibility criteria. We conducted a risk‐of‐bias assessment of the quantitative studies while we assessed the quality of mixed methods and qualitative studies through a 5‐item checklist adapted from the CASP Qualitative Checklist. We did not exclude studies due to quality issues. Nineteen quantitative studies allowed the extraction of 346 effect sizes, classified into predictors and correlates. The data synthesis relied on multiple random effects meta‐analyses with inverse variance weighting. The findings from mixed methods and qualitative studied were used to inform, contextualize, and expand the analysis of quantitative studies. Results: The amount and the quality of available evidence were weak, and most studies had a high risk‐of‐bias. Most independent measures were correlates, with possible issues in establishing a causal relation with organized crime membership. We classified the results into categories and subcategories. Despite the small number of predictors, we found relatively strong evidence that being male, prior criminal activity, and prior violence are associated with higher odds of future organized crime recruitment. There was weak evidence, although supported by qualitative studies, prior narrative reviews, and findings from correlates, that prior sanctions, social relations with organized crime involved subjects, and a troubled family environment are associated with greater odds of recruitment. Authors' Conclusions: The available evidence is generally weak, and the main limitations were the number of predictors, the number of studies within each factor category, and the heterogeneity in the definition of organized crime group. The findings identify few risk factors that may be subject to possible preventive interventions.